Rehabilitation Program For People With Mental Disorders Through Religious And Spiritual Planting At Pesantren Dzikrussyifa'asma ' Berojomusti, Lamongan - Riski Maikowati (Fenomena, 2023)
This paper explores the ODGJ Rehabilitation Program through Religious and Spiritual Cultivation at the Dzikrussyifa' asma' Berojomusti, Lamongan; the researcher highlights the healing methods and implementation that have been done. This study uses a qualitative approach. To find out how this transpersonal or spiritual method is carried out, this article analyzes the data taken through observation. Exploratively, in this study, it was found that in terms of healing using therapeutic methods and ruqyah syar'iyah using asthma 'which is taken from the Qur'an and prayers as a horizontal relationship with God, in terms of rehabilitation and treatment here, it is different, but the first stage is the same, namely the assessment stage, the second is classified according to the severity of the mental disorder or not because the healing method is different, the three healing processes are according to the level of mental disorders, the four patients are guided from the social environment and the process of closeness to Allah SWT Of course, through the process of worshiping ubudiah and muamalah, the latter aims to make patients have activities and educate their morals and reduce the risk of disease recurrence.